Analysis of local government accounting disclosure based on international public sector accounting standards (IPSAS) - Ahmad Juanda; Setu Setyawan; Lia Candra Inata (Journal of Accounting and Investment, 2023)
Research aims: This study aims to test and analyze whether there is an effect of government openness, government financing, economic growth, audit opinion, and prior experience with IFRS in the public sector on the level of local government accounting disclosure based on IPSAS.Design/Methodology/Approach: The population in this study was all local governments in Indonesia in 2016-2020. The samples selected for use in this study were 64 local governments, following the sample criteria. The data type was secondary, which was then analyzed using multiple regression analysis.Research Findings: The results of this study exposed that government openness, prior experience with IFRS in the public sector, and audit opinion affected the level of local government accounting disclosure based on international public sector accounting standards (IPSAS). In contrast, government financing and economic growth did not support disclosing financial statements based on IPSAS.Implication: This research can potentially be relevant to the Government Accounting Standards Committee, the central government, local governments, and the community. By assessing the factors influencing the disclosure of local government accounting based on IPSAS, this research can be used as a consideration for Government Accounting Standards Committee in improving related standard regulations and encouraging local governments to implement an accrual-based IPSAS Public Accountant Standard Implementation Strategy.Originality/Value: Research on analyzing factors affecting local government accounting disclosure based on IPSAS, in particular, has not been widely studied in Indonesia, especially using local government objects. Hence, this research in Indonesia is an interesting thing to study further.